A Case Study on Teacher’s Questioning Strategies in an Indonesian Vocational EFL Classroom - Haikal Fikri, Robeirt; Widhiyanto (Acuity: Journal of English Language Pedagogy, Literature and Culture, 2026)
This single-teacher, single-lesson qualitative case study explores how an English teacher at an Indonesian vocational (SMK) school applies questioning strategies and for what pedagogical purposes. One 90-minute classroom session was video-recorded, supported by a semi-structured teacher interview and relevant lesson documents. Data were coded using Miles, Huberman, and Saldaña’s (2014) interactive model, which combines deductive and inductive approaches to categorize teacher questions into procedural, convergent, and divergent types. A total of 42 teacher questions were identified. Procedural questions (≈57%) dominated, managing routines and transitions, while convergent questions (≈24%) checked comprehension through factual responses. Divergent questions (≈19%) promoted extended talk when combined with wait time and peer prompting. Short classroom vignettes illustrated how probing and redirection fostered participation and reflection. Credibility was maintained through the triangulation of observation, interviews, and documentation, as well as member checking of analytic summaries and an audit trail of coding decisions. In vocational EFL contexts with time and proficiency constraints, the strategic use of divergent prompts, accompanied by explicit wait time and scaffolding, can enhance meaningful student contributions without compromising classroom management. This study contributes empirical evidence from an underexplored SMK setting, offering practical insights for English teachers on balancing procedural control with communicative questioning to foster interaction and motivation in vocational classrooms.